Adult education and change of attitudes towards modern agricultural practices - Z. Abubakar, B.; A. Barau, A.; M. Makinta, M.; I. Jega, A. (Agricultural Advances, 2013)
The research was conducted on whether Adult Education programme contributed to change of farmers’ attitudes towards modern Agricultural practices in Jega Local Government Area of Kebbi state, Nigeria. A total of 60 respondents were interviewed using structural questionnaire. The sampled farmers were drawn from three districts namely; Jega, Dangamaji and Kimba. Two villages were randomly selected from each of the districts and ten respondents were chosen form each of the villages. Descriptive statistics, such as frequencies and percentages were used in analyzing the data. The results on the socio-economic analysis revealed, majority (45%) of the respondents fall between age range of 31-45 years with 68.3 are married and most (66.7%) attended Adult Education Programme. On the effectiveness of the programme, most of (65%) of the respondents agreed, thus, the programme was effective which lead 50% of the respondents were able to read and write most (83.3%) believed that, the programme has produced a positive change in their attitudes towards modern agricultural practices. It has been recommended that, the government has been solicited a concerted efforts from the and other stakeholders such as traditional, and religious leaders as well as community development organizations and non-governmental organizations to render maximum support for the success of the programme.